Aplasias treatment, vaginal atresia and hypoplasia with acrylic phalluses - Bunster, Eduardo (2015)
Briefly we consider nine cases of patients operated by congenital or acquired defects that phalluses acrylic vagina were used to keep the vaginal lumen. In three cases the procedure Kirschner-Wagner was used to create neo-vaginas. In some patients, surgery associated with the administration of cortisone to reduce the natural tendency to shrinkage of the vaginal walls, estrogen and vitamin A to turn nutrition and healing of the vaginal mucosa or grafts placed in Thiersh the neo-vagina. Mortality has been nil and morbidity low and unimportant.